A simple method to obtain endophytic microorganisms from field-collected roots - Silvani, Vanesa Analia (2008)
We describe a simple technique for obtaining endophytic microorganisms from field-collected roots. Roots of plant species were surfaced-sterilized, cut into pieces, and then each root piece was transferred to drops of Gel-Gro medium. The number of segments with bacteria and fungi was quantified and those with bacteria and dark septate endophytic (DSE) fungi were plated onto tryptic soy agar(TSA) and malt extract agar (MEA), respectively. When arbuscular mycorrhizal fungi (AMF) grew from root segments, they were inoculated into Ri T-DNA-transformed carrot root cultures. Eight different species of bacteria and five dark septate endophytes were isolated. Thirty AMF isolates were identified and continuous pure cultures established. This easy and inexpensive approach allowed us to culture various endophytic microorganisms in an in vitro system saving time and space.